Hematopoietic stem cell donor with IgA nephropathy: Challenges and management algorithm. (August 2020) - Nampoothiri, Ram V.; Kumar, Vivek; Bharati, Joyita; Lad, Sheetal; Arora, Kajal; Malhotra, Pankaj; Lad, Deepesh
Abstract: Donor safety is of prime importance in allogeneic hematopoietic cell transplantation. The Worldwide Network for Blood and Marrow Transplantation (WBMT) standing committee on donor issues has issued a consensus statement regarding suitability criteria for related adult donors. This committee recommends that donors with a history of immune-mediated glomerulonephritis and abnormal urine tests should preferably undergo bone marrow harvest, to avoid the theoretical risk of granulocyte colony-stimulating factor (G-CSF) induced immune flare-up. We discuss here a unique situation where a related donor with a history of IgA nephropathy (IgAN) insisted on a peripheral blood stem cell harvest. We propose a management plan for this situation, which posed challenges about donor suitability.